The Influence of the Family Core on the Language Acquisition of Deaf Children: A Study on Communication and Bonding (Global Journal of Human-Social Science, 2025)
This qualitative study grounded in a sociocultural perspective investigates the communication challenges faced by families of deaf children A snowball sampling method was employed through which nine mothers of ten deaf children were interviewed The primary objective was to understand the families emotions regarding deafness how they received the diagnosis and the strategies adopted for interacting and communicating with their children A recurring expectation of speech development among family members was observed as well as conflicts between guidance provided by the health and education sectors and the family s own dynamics Reports highlighted a lack of support following diagnosis and continuous efforts to overcome the barriers imposed by reality Considering family communication as an essential element in the development of deaf children the study offers reflections on practices and discourses that continue to deny their identity and limit their potential
Keywords: family; communication; deaf child; brazilian sign language (libras); inclusion